Eco-Tourism Development Strategy Baluran National Park in the Regency of Situbondo, East Java, Indonesia - Adil Siswanto; Moeljadi Moeljadi (International Journal of Evaluation and Research in Education (IJERE), 2015)
Baluran National Park in the regency of Situbondo, East Java-Indonesia, highly prospective for development of sustainable tourism that can improve the welfare of local people. The suitable tourism type is eco-tourism with local people envolvement.The purposes of this study were: 1). To know the local people envolvement in eco-tourism development; 2). To know the potenciesof Baluran National Park; and 3). To formulateEco-tourism Development Strategy.Using the matrix analysis method of IFAS and EFAS, produce a common strategy; SWOT analysis generates alternative strategies. This research was exploring, to formulate policies and programs based internal and external conditions. Data were collected by questionnaire, interview and observation. The number of respondents 25 people who are competent in the field of tourism.The results showed, local people envolvement of Wonorejo, Bajul Mati, Bimo Rejo, Watu Kebo, Sumber Waru and SumberAnyaras buffer villages, in the development of eco-tourism in Baluran National Park needs to be improved through approach, training and community empowerment. Alternative strategy obtained eco-tourism product development strategy; development of basic infrastructure and facilities as well as supporting tourism; tourist market penetration and promotion; increased security; as well as institutional and human resource development strategy of eco-tourism. Eco-tourism development strategy is a strategic priority of generating eco-tourism product development programs and maintaining biological resources.